Reconstructing Marx on Class, Conflict, and Religion: An Islamic Critical Response (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2025)
This article examines Karl Marx's theory of social class, conflict, and his characterization of religion as “the opium of the people,” testing the explanatory reach of that theory against the Islamic intellectual tradition's account of religion's social function. Marx held that capitalist society divides into two structurally antagonistic classes the bourgeoisie, who own the means of production, and the proletariat, who own only their labor and that religion, as a product of this material base, anesthetizes the suffering this antagonism produces while legitimating the rule of the dominant class. Using a qualitative literature-analysis design, the study reads Marx's primary texts alongside contemporary Marxist class theory and the sociology of religion, then places this body of work in critical dialogue with Islamic scholars Ibn Khaldun, Sayyid Qutb, Ali Shariati, Ismail al-Faruqi, Fazlur Rahman, and Azyumardi Azra who contest Marx's reduction of religion to ideological narcosis. The analysis finds that Marx's class framework retains strong explanatory power for reading contemporary economic inequality, including in Indonesia, but that his religious critique, generalized from the European church's historical alliance with ruling power, does not transfer cleanly to traditions in which religion has functioned as a vocabulary of resistance. The article's contribution is twofold: theoretically, it integrates alienation-centered Marxist class theory with Islamic liberationist thought; practically, it offers social movements a framework that takes both economic structure and religious conviction seriously as sources of social transformation.
Keywords: Karl Marx; social class; conflict theory; opium of the people; Islamic liberation theology; religion and ideology; social justice.